Prognositic factors and clinicopathologic characteristics of small gastrointestinal stromal tumor of the stomach: a retrospective analysis of 31 cases in one center - Zhen Huang; Yuan Li; Hong Zhao; Jian-Jun Zhao; Jian-Qiang Cai (Cancer Biology & Medicine, 2013)
Objective:To analyze the clinicopathologic characteristics and prognostic factors of small gastrointestinal stromal tumor (GIST) of the stomach. Methods:A total of 31 small gastric GIST patients, including 10 males and 21 females, with a median age of 58 years (37-81 years), who underwent surgery at any time from 1999 to 2012 were included in this study. The clinical records of the patients were analyzed retrospectively. Results:Abdominal discomfort and pain (10 cases, 32.3%, respectively) were the two most common complaints among the patients. All patients received surgery, 11 received gastric wedge resection, 11 received subtotal gastrectomy, 5 received laparoscopic gastric wedge resection, and 4 received endoscopic submucosal dissection. No severe adverse complication was observed. A total of 29 patients (93.5%) were followed up. During the follow-up, 2 patients were found to exhibit tumor recurrence, and 1 patient had liver metastases. One patient died of tumor progression, while another died of another malignant tumor. Median progression free survival (PFS) time was 120.3 months, and median overall survival (OS) time was 130.4 months. Conclusion:Small gastric GIST has better prognosis. Surgery is the best choice for therapy. Micro-invasive procedures are safe and effective for elective patients. Tumor necrosis, tumor bleeding, and muscle invasion are potential prognostic factors of small gastric GIST.